CODE-SWITCHING IN ENGLISH CLASSROOM - Budi Sampurna (Jurnal Syntax Transformation, 2023)
Code-switching is one of sociolinguitics phenomenon when a a speaker of bilingual or multilingual switch from a language to another one. The research aims to figure out types of teacher’ code-switching in the teaching and learning process in English class. The study applied a case study of qualitative descriptive research. The participant of the research was an English teacher at a state Islamic school in Sumedang. Observation and interview were used to collect the research data, and the data were analyzed based on code-switching theory proposed by Poplack (1980). The study revealed that (1) teacher applied three types of code switching, namely: intrasentential code switching, inter-sentential code switching, and tag switching; (2) the most frequently used types of code switching used was intrasentential code switching followed by inter sentential code switching and tag switching. Code switching is used by the teacher to reduce either students' misunderstanding of the lesson or their difficulty understanding the English lesson offered by the English teachers in the classroom